An analysis into the implications of information technology on the internal audit function: a case study of Bulawayo City Council - Mugiya, Audrey (Midlands State University, 2015)
This research study was triggered by the researcher’s experiences during Work Related Learning at Bulawayo City Council. The researcher observed that although information technology was making business easier for Bulawayo City Council, the impact of information technology on Bulawayo City Council’s audit department was not being addressed. The research made an in-depth review of the literature related to the impact of information technology on internal audit.This review aimed at obtaining information on what other authors who carried the same study said in order to get the required information conversant with current studies. The researcher made use of the descriptive research methods in gathering the information relevant to the study. The techniques employed included the conducting of interviews and the administering of questionnaires. The population utilized in the research was made up of BCC’s Members of the Audit Committee, Chief Internal Auditor, Senior Accountants and Senior IT Technicians. From the findings obtained, the researcher concluded that the internal audit staffs at Bulawayo City Council were failing to keep abreast to the continuous changes in information technology implemented by the organisation hence recommendations were made.